Impact of the “carbon trade—carbon tax” policy package on China’s macroeconomics and carbon emission reduction - Fei, Yanying; Jia, Cao (Frontiers in Environmental Science, 2024)
This study aims to explore the combined impact of single carbon trading policy and "carbon trade-carbon tax" combination policy on China's economy and carbon emission reduction, in order to provide a scientific basis for policy makers. To this end, the paper constructs a single "carbon trading" computable general equilibrium model and a "carbon trade-carbon tax" computable general equilibrium model. In the construction of the model, the economic impact of carbon trading and carbon tax is deeply considered. The "carbon trade-carbon tax" combination policy further promotes emission reduction actions in the coal, power, heavy industry and light industry sectors by significantly raising the cost of carbon emissions in various sectors. In addition, the study also reveals the important role of carbon tax policy in balancing carbon reduction and economic development. Compared with the single carbon trading policy, the introduction of carbon tax policy can promote the emission reduction efforts of various departments more comprehensively, and also contribute to the steady development of the economy. Finally, the study also found that the combined policy of "carbon trade-carbon tax" promoted various industries to reduce carbon emissions through multiple channels and angles, and achieved better environmental benefits. This discovery provides a new strategic direction for the global response to climate change, and also provides a new perspective and thinking for China's international cooperation and competition in the field of carbon emission reduction. Based on the above findings, the study puts forward the following policy recommendations: In the early stage of the implementation of carbon trading policy, lower penalty price and annual emission reduction rate should be adopted to mitigate the impact on the economy; With the advancement of policies and the adaptation of the market, these standards can be gradually raised to achieve better emission reduction results. At the same time, when formulating the carbon tax policy, it should fully consider its specific impact on the economy of various sectors to ensure the smooth implementation of the policy and achieve the expected emission reduction target.